AOTT 2022
DOI: 10.5152/j.aott.2022.22052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for amputation in patients with diabetic foot ulcers: a cohort study from a tertiary center

Abstract: Objective: This study aimed to analyze risk factors for amputation (overall, minor and major) in patients with diabetic foot ulcers (DFUs). Methods: 407 patients with DFUs (286 male, 121 female; mean age = 60, age range = 32-92) who were managed in a tertiary care centre from 2009 to 2019 were retrospectively identified and included in the study. DFUs were categorized based on the Meggit-Wagner, PEDIS, S(AD)SAD, and University of Texas (UT) classification systems. To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…14 Demirkol et al reported higher white blood cell (WBC) and CRP levels in amputation group (major and minor) and higher ESR, elevated creatinine level and increased wound width in major amputation group compared with the limb salvage group. 15 The studied variables as the cause of ulcers were similar in both groups, which aligns with established information.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…14 Demirkol et al reported higher white blood cell (WBC) and CRP levels in amputation group (major and minor) and higher ESR, elevated creatinine level and increased wound width in major amputation group compared with the limb salvage group. 15 The studied variables as the cause of ulcers were similar in both groups, which aligns with established information.…”
Section: Discussionsupporting
confidence: 85%
“…Nather et al reported that history of stroke, age above 60, nephropathy, peripheral vascular disease, above‐the‐threshold HbA1c levels, ankle‐brachial index below 0.8 as significant predictors for major limb amputation 14 . Demirkol et al reported higher white blood cell (WBC) and CRP levels in amputation group (major and minor) and higher ESR, elevated creatinine level and increased wound width in major amputation group compared with the limb salvage group 15 . The studied variables as the cause of ulcers were similar in both groups, which aligns with established information.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 publications from a total of 3245 connected investigations that were examined that met the inclusion criteria and were published between 1998 and 2023 were chosen and included in the study 10‐41 . The results of these researches are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In studies that were considered for the meta‐analysis, 9934 subjects were in the chosen studies' starting point, and 2906 of them were with LEA 10‐41 . Male gender, smoking, previous foot ulcer, osteomyelitis, gangrene, hypertension, and WBCC were significantly shown to be an RF in LEA in subjects with DFUs.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner grading was used to assess ulcer depth, osteomyelitis and necrosis/gangrene on a scale ranging from 0 to 5. Almost all DFU‐related amputation risk studies have highlighted the reliability of the Wagner classification in predicting amputation 16,17 . Because of the ulcer severity that increases with the Wagner classification grade, more extensive wounds often require amputation.…”
Section: Discussionmentioning
confidence: 99%